Innovation in English Language Teaching: The Implementation of Digital Technology in the Classroom - Hafidurrahman, Moh.; Dwiaryanti, Risca (Indo-MathEdu Intellectuals Journal, 2024)
The rapid advancement of technology has transformed various sectors, including education. The journal explores the integration of digital technology in English language instruction (ELT), highlighting its impact on classroom dynamics, student engagement, and overall learning outcomes. This article also discusses the challenges and strategies of effective implementation, providing recommendations for educators aiming to integrate digital technologies that have transformed English language instruction (ELT) by introducing innovative tools that enhance classroom engagement, personalize the learning experience, and provide access to authentic materials. The research method used in this article is a literature research design, which involves a structured process in identifying, analyzing, and interpreting findings related to phenomena. Exploring the benefits of these innovations, including increased student motivation and improved language proficiency. The study concludes with recommendations to effectively combine digital technology with traditional teaching methods to optimize language learning outcomes to improve language mastery through digital innovation. This paper examines the implementation of various technology platforms, such as interactive tools, multimedia resources, and artificial intelligence-enabled applications, in the context of ELT